Aligning Administrative Law and Public Administration: Key to Effectiveness and Public Trust - Esmati, Shahab; Lewa, Inriati; Herawwaty, Herawaty; Khaled, Ahmed; Indrawati, Indrawati (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, 2024)
This study addresses the gap in understanding the synergy between administrative law and public administration in the context of modern governance. While the roles of each field have been widely discussed, their interaction requires further exploration. Through this study, we aim to bridge that gap by examining how administrative law, which regulates administrative actions and policies to ensure legality and justice, can interact with public administration, which focuses on the efficient and equitable implementation of public policies. Using a theoretical approach and case analysis, this research demonstrates that aligning administrative law with public administration not only enhances efficiency and effectiveness but also strengthens public trust in governmental institutions. Conversely, discrepancies between these two fields may lead to inefficiency, corruption, and injustice. Based on these findings, this study underscores the importance of administrative law reforms that emphasize accountability and transparency, as well as the need for continuous education for public officials to maintain this alignment, ultimately contributing to the improvement of governance in a broader context.